The role of food intake regulating peptides in cardiovascular regulation - Mikulášková, B; Maletínská, L; Zicha, J; Kuneš, J (Molecular and cellular endocrinology, 2016)
Obesity is a risk factor that worsens cardiovascular events leading to higher morbidity and mortality. However, the exact mechanisms of relation between obesity and cardiovascular events are unclear. Nevertheless, it has been demonstrated that pharmacological therapy for obesity has great potential to improve some cardiovascular problems. Therefore, it is important to determine the common mechanisms regulating both food intake and blood pressure. Several hormones produced by peripheral tissues work together with neuropeptides involved in the regulation of both food intake and blood pressure. Anorexigenic (food intake lowering) hormones such as leptin, glucagon-like peptide-1 and cholecystokinin cooperate with α-melanocyte-stimulating hormone, cocaine- and amphetamine-regulated peptide as well as prolactin-releasing peptide. Curiously their collective actions result in increased sympathetic activity, especially in the kidney, which could be one of the factors responsible for the blood pressure increases seen in obesity. On the other hand, orexigenic (food intake enhancing) peptides, especially ghrelin released from the stomach and acting in the brain, cooperates with orexins, neuropeptide Y, melanin-concentrating hormone and galanin, which leads to decreased sympathetic activity and blood pressure. This paradox should be intensively studied in the future. Moreover, it is important to know that the hypothalamus together with the brainstem seem to be major structures in the regulation of food intake and blood pressure. Thus, the above mentioned regions might be essential brain components in the transmission of peripheral signals to the central effects. In this short review, we summarize the current information on cardiovascular effects of food intake regulating peptides.
Keywords: kardiovaskulární systém; Animals; biologické modely; Eating; Food intake; Obesity; lidé; Hormones; Models, Biological; přijímání potravy; Humans; peptidy; hormony; zvířata; Sympathetic nervous system; Blood pressure; Anorexigenic peptides; Peptides; Cardiovascular System; Orexigenic peptides